Mechanical exfoliated large scale CVD-Graphene using water-soluble WO3 supporting layer - Kim, Seung Il; Hyeong, Seok Ki; Moon, Ji Yun; Lee, Jae Hyun (Proceedings of the International Display Workshops, 2019)
We will introduce a large area clean graphene transfer method that solves the problems encountered during the transfer process of CVD graphene. WO3 can transfer high-quality graphene synthesized on a Ge substrate without a defect, and there is no chemical etching process due to its water-soluble nature.
Keywords: Chemical-etching process; CVD graphene; Ge substrates; High quality; Transfer method; Transfer process; Watersoluble; Chemical vapor deposition; Graphene; Mechanical exfoliation; Tungsten oxide